2021
DOI: 10.3389/fphar.2020.599760
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Gut Microbiota and Liver Transcriptome by Red Yeast Rice and Monascus Pigment Fermented by Purple Monascus SHM1105 in Rats Fed with a High-Fat Diet

Abstract: Hyperlipidemia can easily cause atherosclerosis and induce cardiovascular and cerebrovascular diseases. Red yeast rice (RYR) contains a variety of active ingredients and is commonly used as medicine and food, and has pharmacological effects such as lowering blood lipids. In this study, we select Monascus strain SHM1105 with a high yield of Monacolin K and monascus pigment (PIG), and studied the effects of the RYR and PIG fermented by this strain on blood lipids, intestinal flora, and liver transcriptome in hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…It is known that Lachnospiraceae members are involved in the production of butyrate and consequently in the SCFA metabolism. Moreover, some authors have described that Lachnospiraceae are related to changes in lipid metabolism, as well as specific nutrients . Likewise, we found that Flavonifactor and Oscillibacter members from the Ruminococcaceae family, which was influenced by Se-supplementation, were positively correlated with steroids (1,24,25-trihydroxyvitamin D2, 5-cholestane-3,7,12,23-tetrol, and 4-hydroxymethyl-4-methyl-5-cholesta-8,24-dien-3-oland) in Abx-Se mice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is known that Lachnospiraceae members are involved in the production of butyrate and consequently in the SCFA metabolism. Moreover, some authors have described that Lachnospiraceae are related to changes in lipid metabolism, as well as specific nutrients . Likewise, we found that Flavonifactor and Oscillibacter members from the Ruminococcaceae family, which was influenced by Se-supplementation, were positively correlated with steroids (1,24,25-trihydroxyvitamin D2, 5-cholestane-3,7,12,23-tetrol, and 4-hydroxymethyl-4-methyl-5-cholesta-8,24-dien-3-oland) in Abx-Se mice.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, some authors have described that Lachnospiraceae are related to changes in lipid metabolism, as well as specific nutrients. 49 Likewise, we found that Flavonifactor and Oscillibacter members from the Ruminococcaceae family, which was influenced by Se-supplementation, were positively correlated with steroids (1,24,25-trihydroxyvitamin D2, 5cholestane-3,7,12,23-tetrol, and 4-hydroxymethyl-4-methyl-5cholesta-8,24-dien-3-oland) in Abx-Se mice. Some authors have reported the link between the stimulation of Ruminococcaceae species and Se-yeast supplementation, contributing to the maintenance of gut health and providing enzymatic ability to degrade cellulose and hemicellulose.…”
Section: Discussionmentioning
confidence: 57%
“…Desulfovibrionaceae, Helicobacter , and Bilophila produce LPS ( 64 67 ). In addition, Mucispirillum and Ruminococcaceae damage the intestinal mucosa ( 68 , 69 ). Oscillibacter and Ruminiclostridium are related to intestinal dysfunction ( 70 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA, which met the experimental requirements, was enriched by Oligo(dT) beads and reverse transcribed to cDNA immediately after fragmenting into short fragments. The synthesis of second-strand cDNA, puri cation of cDNA fragments, ampli cation of cDNA, and sequencing by Illumina HiSeq TM 2500 were completed by Gene Denovo Biotechnology Co. (Guangzhou, China) according to Yang et al (2021). Reads were mapped to the ribosome RNA (rRNA) database by Bowtie2 (Langmead and Salzberg, 2012).…”
Section: Transcriptome Library Construction Sequencing and Bioinforma...mentioning
confidence: 99%